Identification of key transcription factors, including DAL80 and CRZ1, involved in heat and ethanol tolerance in Saccharomyces cerevisiae - Rong-Rong Chen; Li Wang; Xue-Xue Ji; Cai-Yun Xie; Yue-Qin Tang (Biotechnology for Biofuels and Bioproducts)
Abstract Background High temperature and ethanol are two critical stress factors that significantly challenge bioethanol production using Saccharomyces cerevisiae. In this study, the tolerance mechanisms of the multi-tolerant S. cerevisiae strain E-158 to heat stress and combined heat-ethanol stress were investigated using comparative transcriptomics. Results Under heat stress at 44 °C, glucose transport and reactive oxygen species (ROS) scavenging were significantly upregulated, while gluconeogenesis, acetate formation, and dNDP formation showed significant downregulation. Under combined heat (43 °C) and ethanol (3% v/v) stress, glucose transport, glycolysis, acetate formation, peroxisome activity, ROS scavenging, and ribosome synthesis were significantly upregulated, while glycerol formation, cellular respiration and dNDP formation exhibited significant downregulation. Fourteen transcription factors (TFs), considered to play a key role in both stress conditions, were individually overexpressed and deleted in S. cerevisiae strain KF-7 in this study. Among these TFs, Gis1p, Crz1p, Tos8p, Yap1p, Dal80p, Uga3p, Mig1p, and Opi1p were found to contribute to enhanced heat tolerance in S. cerevisiae. Compared with KF-7, strains overexpressing DAL80 and CRZ1 demonstrated markedly improved fermentation performance under stress conditions. Under heat stress at 44 °C, glucose consumption increased by 10% and 12%, respectively, for strains KF7DAL80 and KF7CRZ1, while ethanol production increased by 12% and 15%, respectively, compared to KF-7. Under combined stress conditions of 43 °C and 3% (v/v) ethanol, glucose consumption increased by 67% and 44%, ethanol production by 116% and 77%, and ethanol yield by 29% and 22%, respectively, for KF7DAL80 and KF7CRZ1 compared to KF-7. KF7CRZ1 performs comparably to E-158, while KF7DAL80 outperforms E-158. Conclusions This study provides valuable theoretical insights and identifies critical TF targets, contributing to the development of robust S. cerevisiae strains for improved bioethanol production.